2019
DOI: 10.1002/jcp.28990
|View full text |Cite
|
Sign up to set email alerts
|

Pyridoxine/pyridoxamine 5′‐phosphate oxidase (Sgll/PNPO) is important for DNA integrity and glucose homeostasis maintenance in Drosophila

Abstract: Pyridoxine/pyridoxamine 5′-phosphate oxidase (PNPO) and pyridoxal kinase (PDXK) cooperate to produce pyridoxal 5′-phosphate (PLP), the active form of vitamin B6. PDXK phosphorylates pyridoxine, pyridoxamine, and pyridoxal by producing PNP, PMP, and PLP, whereas PNPO oxidizes PNP, PMP, into PLP. We previously demonstrated that PDXK depletion in Drosophila and human cells impacts on glucose metabolism and DNA integrity.Here we characterized sgll, the Drosophila ortholog of PNPO gene, showing that its silencing b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 37 publications
3
34
0
Order By: Relevance
“…Moreover, the finding that insulin signaling is reduced in the dPdxk mutant larvae, suggested that dPdxk mutants might represent a new model of T2D [45]. In agreement with these results, the silencing of sgll by RNA interference produced diabetic hallmarks, such as hyperglycemia, reduced body size, and altered lipid metabolism [46]. Moreover, vitamin B6 administration rescues diabetic phenotypes in both Pdxk and Sgll depleted individuals, whereas the treatment with the PLP inhibitor 4-deoxypyridoxine (4-DP) causes hyperglycemia in wild type individuals [45,46,51].…”
Section: Mutations In Genes Involved In Vitamin B6 Synthesis Cause DIsupporting
confidence: 70%
See 2 more Smart Citations
“…Moreover, the finding that insulin signaling is reduced in the dPdxk mutant larvae, suggested that dPdxk mutants might represent a new model of T2D [45]. In agreement with these results, the silencing of sgll by RNA interference produced diabetic hallmarks, such as hyperglycemia, reduced body size, and altered lipid metabolism [46]. Moreover, vitamin B6 administration rescues diabetic phenotypes in both Pdxk and Sgll depleted individuals, whereas the treatment with the PLP inhibitor 4-deoxypyridoxine (4-DP) causes hyperglycemia in wild type individuals [45,46,51].…”
Section: Mutations In Genes Involved In Vitamin B6 Synthesis Cause DIsupporting
confidence: 70%
“…By considering that PLP is both an antioxidant molecule and a cofactor for enzymes involved in DNA metabolism, it is expected that its reduced availability can contribute to increase DNA damage associated with diabetes. Studies in Drosophila and human cell cultures helped to gain evidence in support of this hypothesis, demonstrating that PLP deficiency can cause DNA damage throughout the formation of AGEs [45,46]. We demonstrated in fact that PLP deficiency in Drosophila and human cultured cells, trigger the formation of chromosome aberrations (CABs).…”
Section: Vitamin B6 and Dna Damage In Diabetesmentioning
confidence: 84%
See 1 more Smart Citation
“…Another study [131] showed that folate supplementation was able to alleviate mitochondrial dysfunction in a Parkinson fly model. However, to our knowledge, only vitamin B 6 has been studied in detail in a Drosophila model with the aim to understand cellular and molecular mechanisms at the basis of its beneficial effect on human diseases [132][133][134][135]. royalsocietypublishing.org/journal/rsob Open Biol.…”
Section: Drosophila As a Model System To Study The Effects Of B 6 Depmentioning
confidence: 99%
“…AGEs have been associated with diabetic complications and are quenched by PLP and PM [51,52]. Interestingly, α-lipoic acid, a compound able to decrease AGE formation, rescues not only AGEs but also CABs in brains from dPdxk 1 mutants, Sgll-depleted individuals and 4-DP-fed larvae [132,135]. Taken together, these findings suggested that in low PLP conditions, CABs are mostly produced by hyperglycaemia, which in turn promotes AGE accumulation that causes DNA damage [132,135] (figure 4).…”
Section: Mechanisms Through Which Vitamin B 6 Protects From Dna Damagementioning
confidence: 99%